2016
DOI: 10.15644/asc50/3/2
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Career Perceptions of Dental Students at the School of Dental Medicine University of Zagreb, Croatia

Abstract: The obtained data can be used for the further improvements in the quality of dental study curricula and teaching process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
2
14
0
1
Order By: Relevance
“…This factor is prime as it eclipses all supposed barriers and hurdles such as socio-cultural norms, life stage priorities and personal motivations. Although congruent with researches that identify financial gains as one of the reasons that motivate the choice of a dental career [14] [15] [16]; in our study we see that it plays out in a more nuanced gender-specific and cultural context explicit manner. At a primary level, working is associated with income while passion, drive, motivations for the work are abstract notions that occupy a secondary but equally vital plane.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This factor is prime as it eclipses all supposed barriers and hurdles such as socio-cultural norms, life stage priorities and personal motivations. Although congruent with researches that identify financial gains as one of the reasons that motivate the choice of a dental career [14] [15] [16]; in our study we see that it plays out in a more nuanced gender-specific and cultural context explicit manner. At a primary level, working is associated with income while passion, drive, motivations for the work are abstract notions that occupy a secondary but equally vital plane.…”
Section: Discussionsupporting
confidence: 88%
“…This Theme Has Two Sub-Categories 1) Role of provider: The financial lucrative nature of dentistry, commonly cited as an important reason for becoming a dentist [14] [15] [16], was not alluded to in this study, although it was definitely mentioned as a very beneficial outcome by working, older dentists under the core theme of economic need.…”
Section: Peripheral Theme Ii: Cultural Normsmentioning
confidence: 97%
“…Research with both dental students [7][8][9]11,[13][14][15]17,30,31,[34][35][36][37][38] and dental hygiene students 15,26,27 found that this motivation appeared frequently. a unique opportunity to gain a better understanding of these issues.…”
Section: Discussionmentioning
confidence: 99%
“…An example of a motivation many authors had identified before was to help others. Research with both dental students [7][8][9]11,[13][14][15]17,30,31,[34][35][36][37][38] and dental hygiene students 15,26,27 found that this motivation appeared frequently. However, the use of open-ended responses in our study enabled the emergence of previously largely neglected issues, such as wanting a profession in the health care field 31 and being motivated by own dental experiences, 26,39,40 as well as previously unidentified issues such as being motivated by an interest in science.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered as a convenient profession for maintaining a balance between work and family life, and it gives a great opportunity for meeting people on a regular basis. 1,2 Dental work is a unique social combination of clinical practice, personal traits, and emotions of a health care provider and its recipient.…”
Section: Introductionmentioning
confidence: 99%